Is e-sport a part of sports? - Fizi, Resti Molina; Suherman, Wawan Sundawan; Nanda, Fitri Agung (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2021)
The purpose of this study is to describe the e-sports view of an athlete, the athlete in question is someone who is engaged in sports involving physical activity and movement with national scale achievements. The method in this research is observational with a quantitative descriptive design. The sample in this study amounted to 158 National athletes of Riau Province. The sampling technique represents all sports in Riau Province which are selected based on being in the appropriate situation, time, and place, with the purposive sampling technique. In this study, using a questionnaire instrument with a Likert scale, there were four category assessments, namely strongly agree, agree, disagree, strongly disagree. The data analysis used is a survey method carried out with a questionnaire and the scores obtained and an analysis of the e-sport category using the SPSS 25 application. The results reveal that sportsmen view e-sport as a sport even though there is no strenuous physical activity but there is light physical activity in it. especially in motor movement. The percentage acquisition of 14.6% is good. Then in the sufficient category, the percentage is 25.9%. While the moderate category of the presentation was 30.4%. For the category less the percentage is 20.9%. For the last category is bad 8.2%. The results reveal that sportsmen agree that e-sport is a sport. The results of the study are expected to be able to solve perceptions about e-sport in which there is no physical activity in it, which is a sport.